The Intellectual Traces of Women in the Golden Age of Islam: From Science to Cosmopolitan Culture - Kusuma, Zulfasari; Handayani , Safarah Arum; Aslam, Muhammad; Salleh, Nur Fatimah binti (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
Studies of classical Islamic historiography have been biased in placing men at the center of intellectual narratives. At the same time, women’s contributions have been less systematically explored, resulting in a partial understanding of the dynamics of scholarship during the Islamic Golden Age from the 8th to 14th centuries CE. This study aims to comprehensively reconstruct the role and contribution of women in the fields of science and cosmopolitan culture, focusing on intellectual centers such as Baghdad, Cairo, Andalusia, and Damascus. Using qualitative-historical methods with thematic analysis, this study examines primary manuscripts such as biographies of scholars, scientific treatises, records of hadith transmissions, and relevant secondary literature to uncover concrete traces of women in scientific networks. The findings show that women not only played roles as teachers, hadith transmitters, and interpreters of religious texts, but also contributed to medicine, philosophy, mathematics, and the arts, even gaining recognition on par with male scholars through evidence of attribution of works, participation in scientific assemblies, and cultural patronage. Furthermore, their involvement in discussions across languages ​​and ethnicities strengthened a pluralistic and open intellectual tradition. However, limited access to some manuscripts and attribution issues hinder more quantitative data collection. In conclusion, women’s contributions during this period are an integral part of Islamic intellectual history and require further reconstruction through prosopographic studies and scholarly network mapping to enrich contemporary academic discourse and inspire the strengthening of the role of modern Muslim women.